Thermodiffusion of citrate-coated γ-Fe2O3 nanoparticles in aqueous dispersions with tuned counter-ions – anisotropy of the Soret coefficient under a magnetic field. Issue 4 (11th January 2019) - Kouyaté, M.; Filomeno, C. L.; Demouchy, G.; Mériguet, G.; Nakamae, S.; Peyre, V.; Roger, M.; Cēbers, A.; Depeyrot, J.; Dubois, E.; Perzynski, R.
Abstract : Soret coefficient is modulated in sign by the counterion nature and in magnitude by volume fraction and applied magnetic field; single-particle and thermoelectric contributions are sorted out. Abstract : Under a temperature gradient, the direction of thermodiffusion of charged γ-Fe2 O3 nanoparticles (NPs) depends on the nature of the counter-ions present in the dispersion, resulting in either a positive or negative Soret coefficient. Various counter-ions are probed in finely tuned and well characterized dispersions of citrate-coated NPs at comparable concentrations of free ionic species. The Soret coefficient S T is measured in stationary conditions together with the mass-diffusion coefficient D m using a forced Rayleigh scattering method. The strong interparticle repulsion, determined by SAXS, is also attested by the increase of D m with NP volume fraction Φ . The Φ -dependence of S T is analyzed in terms of thermophoretic and thermoelectric contributions of the various ionic species. The obtained single-particle thermophoretic contribution of the NPs (the Eastman entropy of transfer Ŝ NP ) varies linearly with the entropy of transfer of the counter-ions. This is understood in terms of electrostatic contribution and of hydration of the ionic shell surrounding the NPs. Two aqueous dispersions, respectively, with S T > 0 and with S T < 0 are then probed under an applied field H⃑, and an anisotropy of D m and of S T is induced while the in-field system remains monophasic. Whatever the H⃑ -direction (parallel or perpendicular to the gradients and ), the Soret coefficient is modulated keeping the same sign as in zero applied field. In-field experimental determinations are well described using a mean field model of the interparticle magnetic interaction.